Work process and management competences of the nurses in the family health strategy - Marcilene de Paula; Aida Maris Peres; Elizabeth Bernardino; Elizabete Araújo Eduardo; Silvânia Terezinha Silva Macagi (Universidade Federal do Ceará, 2013)
The objective was to identify the dimension of the process of nursing work in a unit of the Family Health Strategy and correlate the necessary competences for the development of managerial activities. It is a descriptive study using the technique of non-participant observation during 160 hours of activities of four nurses from a unit of the Family Health Strategy, from March to May, 2011. The results showed that the care dimension holds 42% of the time spent by nurses in their activities, followed by management (33%), education (20%) and political participation (2.5%). In managerial dimension, managerial competences were classified as follows: communication (55%), leadership (33%), permanent education (8%) and decision making (4%). These competences are interrelated and developed together with administrative functions: planning, coordination, direction and control. For the development of their attributions in the Family Health Strategies the nurse professionals uses administrative tools demanding constant mobilization of different competences.